2013
DOI: 10.1111/pace.12280
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prophylaxis Topical Antibiotics in Cardiac Device Implantation

Abstract: Careful skin preparation prior to incision is important, whereas the use of topical antibiotics after closure has not shown significant benefit. Patients with malignancy and longer procedural times are more likely to develop infection. There is a trend for less infection with cephalic approach. Systemic antibiotics with staphylococcal coverage are needed as most of the wound culture positive infections are caused by Staphylococcus species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…40 Observational data and meta-analyses support this finding. 4,18,19,41,42 Supporting evidence for using topical antibiotics is lacking; 43 however, recently a promising development has been introduced. The TYRX TM Envelope is an antibacterial envelope releasing minocycline and rifampin in the generator pocket after CIED implantation.…”
Section: Peri-operativementioning
confidence: 99%
“…40 Observational data and meta-analyses support this finding. 4,18,19,41,42 Supporting evidence for using topical antibiotics is lacking; 43 however, recently a promising development has been introduced. The TYRX TM Envelope is an antibacterial envelope releasing minocycline and rifampin in the generator pocket after CIED implantation.…”
Section: Peri-operativementioning
confidence: 99%
“…The complication rates associated with pacemaker or implantable cardioverter‐defibrillator generator REPLACEments and upgrade procedures (REPLACE) registry similarly found no difference in infection rate between those who received postoperative antibiotics and those who did not . In the third study, the role of topical antibiotic was studied in 1008 patients . Enrolled patients received a standard IV preoperative antibiotic prophylaxis and were then randomized into four groups receiving either povidone‐iodine, neomycin ointment, a sterile nonadherent pad, or placebo ointment after procedure.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Several observational trials as well as a randomized placebo-controlled trial have shown that the use of various topical antibiotics after the procedure showed no benefit on the rate of CIED infection. 26,27 The REPLACE registry, has demonstrated that at 6-month follow-up, hospitals with high CIED infection rates had sicker patients and lower overall procedural volume. 19 …”
Section: Procedures Relatedmentioning
confidence: 99%